Sosialisasi Desain Visual Tata Bangunan Berbasis Budaya Lokal di Desa Tlogopatut Gresik - Syaifuddin zuhri; Imam Ghozali; Joumil Aidil Saifuddin (Universitas Lancang Kuning, 2022)
Tlogopatut village is a village in Gresik which good economic growth with many historical buildings. The growth of the community's economy has resulted commercial buildings along the main road. The visual of commercial buildings is not accompanied by control the appearance of the building that’s impact to the chaotic of the visual of city. Preservation of historic buildings is an effective way to control the visual of buildings and be a promotion. Increasing public appreciation in controlling the values ​​of old buildings on the visual of the city can be do with socialization, counseling, design consultation and make a visual design to the village. First activity is socialization to understanding of potentials historic buildings. Second, inform the results of the design of the visual arrangement of the building which from the potentials of the old building. Third, conduct consultations in arranging the appearance of the building that’s a local characteristics.